Characteristic Investigation and Torque Distribution Diagram-Based Computational Method for Continuously Variable Power-Split Transmission. (28th February 2022) - Li, Qingtao; Liang, Li; Li, Chao; Li, Runtao; Yan, Chongyong; Liu, Shengzhen
Abstract : The key parameter of power-split transmission is the planetary ratio. To obtain various planetary ratios in one transmission system, people use complex systems with multiple planetary gear trains, clutches, and brakes. Another solution is replacing the planetary gear train with a planetary traction drive. However, the participation of the planetary traction drive brings about creep and spin motion, which increase the difficulty of precise calculation. In this study, we investigate the relationships between torques and speeds. Then, we derive the torque and speed distribution formulas that consider the influence of spin torque and creep motion. This study is the first step to precisely calculate the emerging power-split transmission with the planetary traction drive. Based on a contact model and a proposed torque distribution diagram method, this study proposes a fast computational method for calculating the performance of the new continuously variable power-split transmission. The results show that the proposed torque distribution diagram-based computational method is feasible, and the planetary traction drive can be a competitive power-split device for power-split transmission.